Influence of temperature on the oxidation behaviour of a ferritic-martensitic steel in supercritical water. (December 2016) - Zhu, Zhongliang; Xu, Hong; Jiang, Dongfang; Mao, Xueping; Zhang, Naiqiang
Highlights: The oxidation kinetics of P92 steel follow a near-parabolic law in supercritical water. The rate-controlling step for oxidation is the outward diffusion of iron ions through a spinel lattice. Temperature has a significant impact on the morphology of the oxide scale. Abstract: The oxidation behaviour of a ferritic-martensitic steel exposed to deaerated supercritical water at 560–650 °C and 25 MPa was investigated. A double-layered oxide formed on all samples, consisting of an Fe-rich outer magnetite layer and a Cr-rich inner oxide layer. The temperature had a strong influence on the oxidation rate and morphology of the oxide films. The oxidation kinetics showed nearly parabolic behaviour. The calculated activation energy indicated that the oxidation rate-controlling step was the outward diffusion of Fe 2+ and Fe 3+ ions through the spinel lattice. The mechanism behind the temperature dependence of the oxidation is further discussed.